The Stalin era - Boobbyer, Philip (Routledge sources in history, 2000)
"The Stalin Era provides a wide-ranging history of Stalin's dictatorship in the Soviet Union. Drawing upon a great range of primary sources, this book is an account of Stalinist thought and policy, and their effects. It also puts the Stalin regime into the context both of Lenin's period of rule and of the longer-term continuities of Russian history."--BOOK JACKET.